IMPORTANCE PERFORMANCE ANALYSIS (IPA) APPLICATION FOR EXTERNAL EVALUATION OF ORGANISATION’S MISSION STATEMENT PERFORMANCE - Gogor Arif Handiwibowo (Journal of Research and Technology, 2017)
One of strategic formulation result is organization’s mission statements. In the implementation, organization’s mission statements are distributed and implemented in organization activities. Evaluation is needed to describe the evaluation of all organization activities based on mission statements. Overall, evaluation is needed to ensure the alignment of formulation to implementation. Importance Performance Analysis (IPA) method is proposed to evaluate the achievement of organization’s mission statements from external perspective. This method is implemented evaluate part of mission statements at MMT-ITS Department from the students’ perspective. The evaluation analyze the gap between importance and performance level of the mission statements.